The Immune-associated nucleotide-binding 9 Protein Is a Regulator of Basal Immunity in Arabidopsis thaliana. - Wang, Yuanzheng; Li, Yansha; Rosas Díaz; Cáceres Moreno, Carlos; Lozano-Durán, Rosa; Macho, Alberto P. (American Phytopathological Society, 2018)
A robust regulation of plant immune responses requires a multitude of positive and negative regulators that act in concert. The immune-associated nucleotide-binding (IAN) gene family members are associated with immunity in different organisms, although no characterization of their function has been carried out to date in plants. In this work, we analyzed the expression patterns of IAN genes and found that IAN9 is repressed upon pathogen infection or treatment with immune elicitors. IAN9 encodes a plasma membrane-localized protein that genetically behaves as a negative regulator of immunity. A novel ian9 mutant generated by CRISPR/Cas9 shows increased resistance to Pseudomonas syringae, while transgenic plants overexpressing IAN9 show a slight increase in susceptibility. In vivo immunoprecipitation of IAN9-green fluorescent protein followed by mass spectrometry analysis revealed that IAN9 associates with a previously uncharacterized C3HC4-type RING-finger domain-containing protein that we named IAN9-associated protein 1 (IAP1), which also acts as a negative regulator of basal immunity. Interestingly, neither ian9 or iap1 mutant plants show any obvious developmental phenotype, suggesting that they display enhanced inducible immunity rather than constitutive immune responses. Because both IAN9 and IAP1 have orthologs in important crop species, they could be suitable targets to generate plants more resistant to diseases caused by bacterial pathogens without yield penalty.
https://openpolicyfinder.jisc.ac.uk/id/publication/10349
Keywords: Arabidopsis thaliana - Aspectos moleculares; Plasma membrane receptor; Salicylic acid; Vesicle trafficking; Innate immunity